The Principle of Al-Darar Yuzal (الضرر یزال) in Islamic Family Law Perspective: Implications of Premarital Medical Testing for the Prevention of Sickle Cell Disease and Implications on Marriage: - Aishatu Abubakar Kumo; Ahmad Muhammad Jungudo; Murtala Muhammad Abdu (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Premarital medical testing serves as a preventive mechanism whereby prospective couples undergo medical screening to detect genetic, infectious, and blood-transmitted diseases such as Sickle Cell Disease (SCD). This practice has become increasingly relevant in light of the rising number of children born with genetic disorders, particularly in regions with high SCD prevalence such as sub-Saharan Africa. While premarital screening has sparked debate within certain cultural and religious contexts, Islamic jurisprudence offers a compelling framework that supports such preventive health measures. This study aims to examine the legal and ethical justification of premarital genetic testing from the standpoint of Islamic law, focusing specifically on the maxim Al-Darar Yuzal (harm must be eliminated), one of the five major legal maxims (Al-Qawa’id Al-Kubra) in Islamic jurisprudence. Employing a qualitative and doctrinal research methodology, the study utilizes content analysis of classical juristic texts, contemporary academic literature, and public health data. Through this approach, the paper critically explores arguments both for and against premarital testing while highlighting the relevance of Islamic principles that prioritize the elimination of harm and the preservation of public health. The findings suggest that Islam not only permits but encourages any lawful measure aimed at safeguarding human health, provided it does not contradict the core teachings of the Shari’ah. Ultimately, the study concludes that premarital genetic testing especially for conditions like SCD is not only compatible with Islamic teachings but also aligned with the broader objectives of Shari’ah (Maqasid al-Shari’ah), particularly the protection of life and progeny. As such, both government and religious institutions should actively promote premarital screening as a responsible and preventive step toward ensuring healthy future generations.